Combined Alkylating Agents as a Resolution for Highly Selective N-Alkylation of 2-Hydroxybenzaldehyde Acylhydrazones - Zhang, Qiao Y.; Cheng, Xin J.; Zhao, Xin Y.; Wu, La M.; Jin, Long F.; Zhang, Hui J. (Synlett, 2019)
Although 2-hydroxybenzaldehyde acylhydrazones, such as salicylaldehyde acylhydrazones, are intriguing bioactive molecules, few of their N-alkylated derivatives are known, and only methyl analogues have been reported previously. We achieved selective N-alkylation of 2-hydroxybenzaldehyde acylhydrazones, as their Fe(III) complexes, by using combinations of alkylating agents (for example, an alkyl bromide and a dialkyl sulfate). Fifteen substrates were examined, and 45 new 2-hydroxybenzaldehyde acyl(alkyl)hydrazones were synthesized in moderate to good yields. In all cases, the target products were obtained exclusively, and no O-alkylation byproducts were produced. The method provides an efficient way of preparing 2-hydroxybenzaldehyde acyl(alkyl)hydrazones.
Keywords: alkylation; regioselectivity; medicinal chemistry; salicylaldehyde acylalkylhydrazones; hydrazones